Environment and Culture, a Cross-Sectional Survey on Drivers of Burnout in Pediatric Intensive Care - Dalal, Nupur N.; Gaydos, Laura M.; Gillespie, Scott E.; Calamaro, Christina J.; Basu, Rajit K. (Journal of Pediatric Intensive Care, 2021)
Very little data is available to understand the drivers of burnout amongst health care workers in the pediatric intensive care unit. This is a survey-based, cross-sectional, point-prevalence analysis within a single children's health system with two free-standing hospitals (one academic and one private) to characterize the relationship of demographics, organizational support, organizational culture, relationship quality, conflict and work schedules with self-reported burnout. Burnout was identified in 152 (39.7%) of the 383 (38.7%) respondents. No significant relationship was identified between burnout and demographic factors or work schedule. A more constructive culture (odds ratio [OR], 0.84; 95% confidence interval [CI], 0.77–0.90; p < 0.001), more organizational support (OR, 0.94; 95% CI, 0.92–0.96; p <0 0.001), and better staff relationships (OR, 0.54, 95% CI, 0.43–0.69; p < 0.001) reduced odds of burnout. More conflict increased odds (OR, 1.25; 95% CI, 1.12–1.39; p < 0.001). Less organizational support (Zβ = 0.425) was the most important factor associated with burnout overall. A work environment where staff experience defensive cultures, poor relationships, more frequent conflict, and feel unsupported by the organization is associated with significantly higher odds of burnout in pediatric critical care. The effect of targeted interventions to promote constructive cultures, collegiality, and organizational support on burnout in pediatric intensive care should be studied.
Keywords: burnout; critical care; neonatal intensive care; organizational culture; Maslach